Feminist thinking in late seventh-century China. Issue 1 (9th February 2015) - Peng, Niya; Yu, Tianyuan; Mills, Albert
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to offer novel insights into: knowledge of proto-feminism through description and analysis of the rule of the seventh century female Emperor Wu Zetian; postcolonial theory by revealing the existence and proto-feminist activities of a non-western female leader; and the literature on gender and invisibility through a study of a leading figure that is relatively unknown to western feminists and is even, in feminist terms, something of a neglected figure. Design/methodology/approach – In order to examine Wu's proto-feminist practices as recorded in historical materials, we use critical hermeneutics as a tool for textual interpretation, through the following four stages: choosing texts from historical records and writings of Wu; analyzing the historical sociocultural context; analyzing the relationship between the text and the context; and offering a conceptual framework as a richer explanation. Findings – Wu's life activities demonstrate proto-feminism in late seventh century China in at least four aspects: gender equality in sexuality, in social status, in politics, and women's pursuit of power and leadership. Research limitations/implications – Future research may dig into the paradox of Wu's proto-feminist practices, the relationship between organizational power and feminism/proto-feminism, and the ways in which Wu's activities differ from other powerful women across cultures, etc. Practical implications – The study encourages a rethink of women and leadership style in non-western thought. Social implications – The study supports Calás and Smircich's 2005 call for greater understanding of feminist thought outside of western thought and a move to transglobal feminism. Originality/value – This study recovers long lost stories of women leadership that are "invisible" in many ways in the historical narratives, and contributes to postcolonial feminism by revealing the existence of indigenous proto-feminist practice in China long before western-based feminism and postcolonial feminism emerged.